Industrial Online Gambling as Dangerous Cyber Crime in Indonesia - Susanto, Budi; Suhana; Husain, Azis (Ann Publisher, 2024)
Currently, the reality of a lifestyle that tends to be consumptive, especially combined with the increase in daily necessities due to the speedy rate of economic inflation, makes everyone want to achieve everything practically and instantly, or they think it is easy. One of the things done is gambling. Gambling is a criminal act, i.e., risking a certain amount of money where the winning party will get the entire bet. Gambling can also be referred to as a matter of luck, as it can harm society and the nation's moral values. This crime also disturbs public order, peace, and security. In addition, the influence of gambling does not only affect adults but the impact of gambling also affects children. The Online Gambling Task Force (Satgas), formed by President Joko Widodo and the Financial Transaction Reporting and Analysis Center (PPATK), found several findings related to online gambling in Indonesia. Among them, the turnover of online gambling money reached Rp 600 trillion, and the flow of funds flowed to several countries abroad, including several ASEAN countries such as Cambodia, Vietnam, Thailand, and the Philippines. Online gambling turnover will reach 600 T, and the January-March 2024 period will reach 100 T. A total of 2,370,000 residents are addicted to online gambling, 2% (800,000) of children under the age of 10 years.